2008
DOI: 10.1074/jbc.m802621200
|View full text |Cite
|
Sign up to set email alerts
|

The Three Mitochondrial Encoded CcmF Proteins Form a Complex That Interacts with CCMH and c-Type Apocytochromes in Arabidopsis

Abstract: Three reading frames called ccmF N1 , ccmF N2 , and ccmF c are found in the mitochondrial genome of Arabidopsis. These sequences are similar to regions of the bacterial gene ccmF involved in cytochrome c maturation. ccmF genes are always absent from animal and fungi genomes but are found in mitochondrial genomes of land plant and several evolutionary distant eukaryotes. In Arabidopsis, ccmF N2 despite the absence of a classical initiation codon is not a pseudo gene. The 3 ccmF genes of Arabidopsis are expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 65 publications
1
55
0
Order By: Relevance
“…There were almost no changes in the transcripts of atp4, atp6-1, atp6-2, atp9, and nad4L. The only downregulated transcript in the shot1-2 mutant was the ccmF C transcript, which encodes a subunit of a protein complex reported to be involved in cytochrome c maturation (Rayapuram et al, 2008).…”
Section: Mutation Of a Chloroplast Mterf Does Not Confer Heat Tolerancementioning
confidence: 89%
“…There were almost no changes in the transcripts of atp4, atp6-1, atp6-2, atp9, and nad4L. The only downregulated transcript in the shot1-2 mutant was the ccmF C transcript, which encodes a subunit of a protein complex reported to be involved in cytochrome c maturation (Rayapuram et al, 2008).…”
Section: Mutation Of a Chloroplast Mterf Does Not Confer Heat Tolerancementioning
confidence: 89%
“…C, shown is an elution profile (absorbance at 280 nm as a function of the volume) of a mixture containing His-apoCcmE, FLAGCcmI, and Strep-apocytochrome c 2 from the Sephacryl S200 column in buffer containing 0.01% DDM. Estimation of the molecular masses (kDa) was done according to the calibration of the column using bovine serum albumin (67 kDa), carbonic anhydrase (39 kDa), and horse heart cytochrome c (12. yeast two hybrid screens, revealed that in Arabidopsis thaliana CcmFN2 and CcmH interacted with apocytochrome c (32,33). E. coli CcmH could reduce the disulfide bond of a apocytochrome c-like peptide in vitro (16), and R. capsulatus Cys-less CcmG could co-purify with apocytochrome c 2 (34).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that multiple functions described here provide the rationale for these conservations and observations. Interestingly, in plant mitochondrial genomes, CcmF is separated as two (72) and sometimes three individual ORFs, called CcmF N1 , CcmF N2 , and CcmF C , which form a complex with CcmH (70,121). Has genomic reorganization of the mitochondrial endosymbiont naturally separated multiple functions of the CcmF protein, albeit while still forming a complex?…”
Section: System I: Ccmabcdefghmentioning
confidence: 99%